Section 68a, Land Acquisition Act 1960: A Stumbling Block To Judicial Review? - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 2019)
Section 68A of the Land Acquisition Act 1960 is of rather recent origin. It was inserted into the LAA by the Land Acquisition (Amendment) Act 1991. It reads as follows: Where any land has been acquired under this Act, whether before or after the commencement of this section, no subsequent disposal or use of, or dealing with, the land, whether by the State Authority or by the Government, person or corporation on whose behalf the land was acquired, shall invalidate the acquisition of the land.